Rapid detection of Staphylococcus aureus using a novel multienzyme isothermal rapid amplification technique - Heng, Pengfei; Liu, Jiakai; Song, Zhen; Wu, Chuan; Yu, Xiuzhong; He, Yang (Frontiers in Microbiology, 2022)
Staphylococcus aureus is a common pathogen that causes various infections. Therefore, it is crucial to develop a fast and easy detection method for diagnosing and preventing S. aureus infections. In this study, MIRA assay was developed and validated (specificity; 100%) for the detection of S. aureus with nuc as the target gene. The reaction temperature and reaction time were then optimized, and the best reaction was at 40 °C, 20 min. The assay could detect S. aureus in only 25 min. Additionally, the limit of detection of MIRA was 5×102 CFU/mL, 10-fold lower than that of the traditional PCR. Furthermore, this assay efficiently detected 219 S. aureus of 335 strains obtained from different bacterial samples (detection accuracy; 99.40%). In conclusion, this study provides a rapid and easy-to-operate method for the detection of S. aureus, and thus can be used for the timely diagnosis and prevention of S. aureus infection.